Japanese sentence patterns for JLPT N4: training book - Noboru Akuzawa ([Place of publication not identified] : Amazon Digital Services LLC, 2018)
This is the text book for practicing Japanese with Sentence Pattern Method and Read-aloud Method.Sentence Pattern Method (SPM) is the key to install Japanese grammar rules in your brain.Sentence Pattern Method is the sentence template that contains constants and variables. This is similar to the mathematical formula. Being able to recognize a variety of sentence patterns enhances your ability to use those patterns in your speaking. Sentence Pattern Method helps a learner to convert his/her thoughts in mother tongue into Japanese sentences very easily.However, knowing Sentence patterns is not enough. We need to practice to help set them more firmly in memory. So, this book will tell you how to utilize (3z(BRead-aloud Method(3y (Bto print sentence patterns in your memory and to open the door to boost your Japanese communications skills.s
Keywords: Japanese Sentence Patterns; Japanese language